Infrastructure in Central, Eastern, and Southeastern Europe : Benchmarking, Macroeconomic Impact, and Policy Issues - Ari, Anil.; Bartolini, David; Boranova, Vizhdan; Di Bella, Gabriel (Washington, D.C. : International Monetary Fund, 2020)
CESEE countries lag in terms of infrastructure compared to the EU15, and deficient infrastructure is often cited as a constraint to growth and convergence. Investing in infrastructure is therefore an important long-standing policy issue for the region. In the context of the Covid-19 pandemic, infrastructure investment has also gained some ground as economies look to support activity in the recovery phase once the virus has been contained. Against this backdrop, this project seeks to benchmark infrastructure in CESEE, assess the macro impact of higher infrastructure investment, and discuss policies issues to maximize such impact. First, we benchmark infrastructure in the region versus the EU15, across various infrastructure sectors and using different methodologies. Second, deploying empirical estimates and model-based simulations, we analyze the macroeconomic impact of boosting infrastructure investment. Third, we present an in-depth analysis of policy issues: enhancing public investment management, managing fiscal risks, and mobilizing private sector participation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet